PENINGKATAN LITERASI AKSARA DI DESA MUARA KECAMATAN TELUK NAGA KABUPATEN TANGERANG - Kadarisman Kadarisman; Romi Siswanto (Jurnal Abdimas Bina Bangsa, 2024)
Muara Village, Teluk Naga District, Tangerang Regency, a village located at the end of the Pantai Indah Kapuk II luxury condominium complex, right on the edge of Teluk Naga Beach. The livelihood of the population is mostly traditional fishermen, some are laborers, grocery traders. Local residents prioritize their sons and daughters to help their parents financially by becoming fishermen or casual laborers rather than sending them to school. The presence of the Digital Literacy Program for rural communities is able to increase the capacity, quality and skills of local residents. With digital access, information becomes an inclusive right for all people without exception. In the future, it is hoped that rural communities will have competitiveness, both economically and educationally. This can help reduce the inequality that exists in a rural environment. The Literacy Improvement Program in Muara Village is a form of service to teach illiterate community members to have the skills to write, read, count and analyze, oriented towards daily life by utilizing digital technology. The implementation strategy for eradicating illiteracy that will be implemented is based on integrated tutorials, namely the implementation of learning based on integration between functional literacy education and assistance by families. After students learn to study with tutors, when students return home, their families contribute to assisting them in learning. Benefits of the Literacy Improvement Program: 1) increase local residents' knowledge of reading, writing and arithmetic; 2) accelerate the eradication of illiteracy, especially in Muara village, 3) foster interest, love and passion for reading, writing and arithmetic, 4) Utilize the advantages of digital technology for independent learning activities